IMPLEMENTATION OF TRANSIT ORIENTED DEVELOPMENT (TOD) IN THE JAKARTA SUB-URBAN AREA - Herika Muhamad Taki; Anita Sitawati Wartaman; Marselinus Nirwan Luru; Hanny Wahidin Wiranegara; Apri Zulmi Hardi (Universitas Trisakti, 2024)
The high mobility of sub-urban communities has become the focus of the government to create an effective transportation system by creating a Transit-Oriented Development concept at several stations in sub-urban or supporting cities of DKI Jakarta. Aims: The purpose of this research is to find out whether the Bekasi and Plawad stations which are located in the suburbs are effective for making transit oriented development. Methodology and results: The type of research to be carried out is quantitative and qualitative research, in which the variables in this study will cover the area, the distance between points, the number of trips from each region to the types of transportation modes used by the community. Then, these variables will be analyzed spatially using maps created in the ArcGIS application and compared to be given a score (scoring) in accordance with the provisions of the indicators of the variables that have been determined in this study. Conclusion, significance and impact study: Plawad and Bekasi Stations are considered not feasible to be used as TOD due to inadequate facilities, the train itself is not yet the main transportation and needs to be increased to meet the commuter mobility needs of the people of Bekasi City.